(untitled) (Research, Society and Development, 2022)
Objective: to evaluate potential severe and moderate drug interactions in patients with chronic kidney disease (CKD) not on dialysis and using polypharmacy. Methodology: cross-sectional study carried out in a city in the center-west of Minas Gerais/Brazil. The population consisted of patients with non-dialysis kidney disease treated at the municipal nephrology clinic. Descriptive analysis was used to characterize the sociodemographic, clinical, and laboratory profile of the population. Bivariate logistic regression analysis was applied to determine factors associated with potential drug interactions. Variables with p-value < 0.20 were taken to the multivariate model. Results: Of the total of 75 participants, most were female, elderly and white. Among them, 60% (45/75) were in stage 3A and 3B of kidney disease. No significant association was found between the use of polypharmacy and Estimated Glomerular Filtration Rate (p <0.671). Among the 630 drug prescriptions evaluated, a total of 833 drug interactions (MI’s) were found, with 7.68% (n=64) being severe, 75.27% (n=627) moderate and 17.05% (n= 142) light. Use of polypharmacy was identified in 81.3% (61/75) of patients, with an average of nine medications per patient. Conclusions: high rates of moderate drug interactions were found, in addition to the presence of severe interactions. The association of multiple drugs in pharmacotherapy, especially for elderly patients with kidney disease, is often unavoidable and, therefore, deserves special attention not only from prescribing professionals but also from the entire team in order to safeguard the safety of these patients, avoiding events adverse events related to MIs.